Health research systems in Somaliland: a qualitative study on perspectives of government and non-governmental staff - Ahmed, Soheir H.; Kiruja, Jonah; Solieman, Ayanle; Wangamati, Cynthia Khamala (Frontiers in Health Services, 2023)
ABSTRACT Background: Globally, the importance of effective national health research systems has gained considerable attention. Literature indicates low research output in Africa; Africa accounts for only 2% of the world’s research output and 1.3% of global publications. In Somaliland, where provision of quality healthcare services is crucial, understanding and enhancing the health research system is a critical endeavor. Aim: The aim of this study is to explore the perspectives of government and non-governmental stakeholders on the health research systems in Somaliland. Method: The study employed an exploratory qualitative study design that entailed in-depth interviews with participants. Thirty-four study participants were interviewed; they included key persons in the academic and health sector, government and, international and local non-governmental organizations (NGOs) involved in health research systems. A semi structured interview guide was used to conduct the in-depth interviews with purposively selected participants. The collected data was analyzed thematically. Findings: We found that there was no national health research centre in Somaliland. The country also lacked a national health research policy. There was limited funding for research, funds were mostly from international organisations and researchers’ own funds. In addition, staff working in research centres were ill equipped to conduct research and study participants highlighted the need for national health research governance. Conclusion: This study highlights the importance of health research systems in Somaliland. We recommend the establishment of a national health research institute, development of a national health research policy and priorities, allocation of sufficient and sustainable funding, capacity building of staff and strengthening of the national health research governance in health research systems. Keywords: Health research systems, governmental and nongovernment stakeholders, Somaliland.